Filter ZeRAK for Decreasing Water Hardness and Coliform - Haryono Haryono; Agus Kharmayana Rubaya (Poltekkes Kemenkes Yogyakarta, 2020)
One of chemical requirement for drinking water is hardness. Water with high level hardness isvery dangerous for human health, specifically for kidneys. MPN coliform as one of bacteriologicalrequirements for water quality is an indicator for excreta pollution. The aim of the study was todecrease water hardness and coliform in water wells of Jimbung Villages in Kalikotes, Klaten byinstalling ZeRAK filter, which consists of zeolite, resin, chlorine and activated charcoal. The studywas an experiment with pre-test and post-test design. As a study sample were 45 wells that wereconnected with plumbing in that village. The results show that before the filtration, the average ofwater hardness was 270 mg/l, while post-filtration it was 44 mg/l (84%). Coliform pre-filtrationwere in a range between 111 and 1898 MPN per 100 ml, and after treatment they were between0 and 7 MPN. Statistically, the differences are significant (both p-values <0,001). To conclude,ZeRAK filter used in this study is effective to decrease water hardness and coliform.